Temperature-dependent magnetic and resistive switching phenomena in (La, Ba)MnO3/ZnO heterostructure. (August 2018) - Polek, Taras; Sanchez, Elena H.; Colino, Jose M.; Normile, Peter S.; Lotey, Gurmeet Singh; Tovstolytkin, Alexandr; Nakamura, Yoshinobu; Reddy, Lakshmi; Kaneko, Satoru; Mele, Paolo; Endo, Tamio
Abstract: Electric, magnetic and resonance properties of La0·7 Ba0·3 MnO3 /ZnO heterostructure fabricated on MgO (001) and LaAlO3 (100) substrates by ion-beam sputtering have been studied in the work. Good crystallinity and phase purity of all heterostructure components have been confirmed using X-ray diffraction. Phase separated magnetic state of the manganite layer of heterostructure has been experimentally proved in the temperature region from 300 K down to 3 K. It has been shown that (La, Ba)MnO3 /ZnO bilayer exhibits multi-step resistive switching as voltage exceeds a certain temperature-dependent threshold value. Detailed study of the resistive switching processes has been carried out at room temperature and in the low-temperature region. It is concluded that phase-separated state of manganites is responsible for strong temperature-induced transformation of the features of resistive switching phenomena. Highlights: Electric, magnetic and resonance properties of (La, Ba)MnO3 /ZnO nanostructure fabricated on MgO (001) have been studied. Temperature-dependent magnetic and resistive switching phenomena have been analyzed in detail. Temperature-induced transformation of magnetic state of (La, Ba)MnO3 should be taken into account when analyzing resistive switching effects.